Outcomes of Autologous Fat Grafting for Breast Reconstruction Following Mastectomy: A Systematic Review and Meta-Analysis - Zhirayr J. Margarit, Svetlana V. Levon (Academic Journal of Clinicians, 2025)
Background Autologous fat grafting (AFG) has gained popularity as a technique for breast reconstruction following mastectomy. Understanding its outcomes is essential for optimizing patient care and surgical strategies. Objective This systematic review and meta-analysis aim to evaluate the outcomes of autologous fat grafting for breast reconstruction after mastectomy, focusing on complications, aesthetic results, and patient satisfaction. Methods A comprehensive literature search was conducted across multiple databases, including PubMed, Scopus, and Cochrane Library, for studies published up to 2023. Inclusion criteria encompassed studies that reported on outcomes of AFG in breast reconstruction. Data on complications, aesthetic outcomes (using validated scoring systems), and patient satisfaction were extracted and analyzed. Results A total of 25 studies involving 1,500 patients were included. The overall complication rate was 12%, with the most common complications being infection (4%) and fat necrosis (6%). Aesthetic outcomes were rated as good to excellent in 80% of cases, and patient satisfaction scores averaged 85%. Meta-analysis indicated that higher volumes of fat grafted were associated with improved aesthetic outcomes (p < 0.01). Conclusions Autologous fat grafting for breast reconstruction following mastectomy demonstrates favorable outcomes, with a low complication rate and high patient satisfaction. The technique appears to be a safe and effective option for enhancing aesthetic results in breast reconstruction. Further high-quality, randomized controlled trials are needed to solidify these findings.